Efektifitas Edukasi Senam Kegel dengan Media Video Terhadap Kemampuan Keluarga dalam Merawat Klien dengan Masalah Inkontinesia Urin - Lestari, Anisyah Arum; Lestari , Nina Dwi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Background - Incontinence can cause discomfort in terms of personal hygiene in sufferers. Urinary incontinence requires proper treatment, because if not treated immediately urinary incontinence can lead to complications. such as urinary tract infections, genital skin infections, sleep disturbances, and symptoms of skin redness. Management of this condition can be overcome through non-pharmacological therapy, one of which is by controlling the bladder and sphincter or commonly called Kegel exercises. Purpose – This case study aims to determine the implementation of Kegel exercise education with video media on the ability of families to care for clients with urinary incontinence problems. Methods – This study was conducted using a case study on a male with urinary incontinence. Intervention provided by educating families regarding Kegel exercise movements using video media. Results - The results of this study found that there was an influence on the effectiveness of Kegel exercise education on the knowledge of families who cared for clients with urinary incontinence. Suggestion – This research is expected that families are able to independently practice Kegel exercises that have been taught to help strengthen the pelvic muscles of patients with urinary incontinence